Evaluasi Implementasi Anggaran Berbasis Kinerja dalam Mewujudkan Value For Money pada Pemerintah Daerah Kota Surabaya Periode 2022–2024 - Amilia Setiyawati; Vanny Rezky Pratiwi; Elza Mariska; Adha Sagita Sari; Subaidah Subaidah (Indo Publishing, 2026)
The implementation of performance-based budgeting in the government sector aims to increase transparency, accountability, and effectiveness of state financial management so that every budget allocation is oriented towards measurable performance achievements. However, local government budget management practices in Indonesia still show various problems in terms of efficiency and effectiveness. This study evaluates the level of economy, efficiency, and effectiveness of budget management in the Surabaya City Government for the 2022–2024 period through a Value for Money approach. This study uses a qualitative and descriptive methodology with additional information in the form of the Budget Realization Report (LRA) and the Surabaya City Regional Government Financial Report (LKPD). Data analysis was conducted through the calculation of economic ratios, efficiency ratios, and effectiveness ratios. The results of this study indicate that the economic ratio has been below 100% for three consecutive years (88.83%; 88.19%; 86.94%), thus categorizing it as economical. The efficiency ratio ranges from 99.36%–107.47% and is categorized as less efficient to inefficient. The effectiveness ratio ranges from 88.78%–89.56% and is categorized as quite effective. Overall, the implementation of performance-based budgeting in the Surabaya City Government has met economic and effective standards. However, improvements in efficiency are still needed to ensure optimal implementation of the Value for Money principle.